Prophylaxis of migraine: general principles and patient acceptance - Domenico D’Amico (Dove Medical Press, 2008)
Domenico D’Amico1, Stewart J Tepper21Headache Center, Department of Neurological Sciences, C Besta Neurological Institute, Milan, Italy; 2Center for Headache and Pain, Neurological Institute, Cleveland Clinic Foundation, Cleveland, Ohio, USAAbstract: Migraine is a chronic neurological condition with episodic exacerbations. Migraine is highly prevalent, and associated with significant pain, disability, and diminished quality of life. Migraine management is an important health care issue. Migraine management includes avoidance of trigger factors, lifestyle modifications, non-pharmacological therapies, and medications. Pharmacological treatment is traditionally divided into acute or symptomatic treatment, and preventive treatment or prophylaxis. Many migraine patients can be treated using only acute treatment. Patients with severe and/or frequent migraines require long-term preventive therapy. Prophylaxis requires daily administration of anti-migraine compounds with potential adverse events or contraindications, and may also interfere with other concurrent conditions and treatments. These problems may induce patients to reject the idea of a preventive treatment, leading to poor patient adherence. This paper reviews the main factors influencing patient acceptance of anti-migraine prophylaxis, providing practical suggestions to enhance patient willingness to accept pharmacological anti-migraine preventive therapy. We also provide information about the main clinical characteristics of migraine, and their negative consequences. The circumstances warranting prophylaxis in migraine patients as well as the main characteristics of the compounds currently used in migraine prophylaxis will also be briefly discussed, focusing on those aspects which can enhance patient acceptance and adherence.Keywords: migraine, prophylaxis, preventive therapy, acceptance, adherence